Petroleum and gas field processing - Abdel-Aal, Hussein K. (Marcel Dekker, 2003)
The immediate product extracted from oil and gas wells consists of mixtures of oil, gas, and water that is difficult to transport, requiring a certain amount of field processing. This reference analyzes principles and procedures related to the processing of reservoir fluids for the separation, handling, treatment, and production of quality petroleum oil and gas products. It details strategies in equipment selection and system design, field development and operation, and process simulation and control to increase plant productivity and safety and avoid losses during purification, treatment, sto.
Keywords: Petroleum -- Refining.; Natural gas.; Petroleum engineering.; elektronické knihy; electronic books